1998
DOI: 10.1046/j.1523-1747.1998.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Microvascular Density and Enhanced Leukocyte Rolling and Adhesion in the Skin of VEGF Transgenic Mice

Abstract: Vascular endothelial growth factor (VEGF) has been implicated in the pathologic angiogenesis observed in psoriasis and other chronic inflammatory skin diseases that are characterized by enhanced expression of VEGF by epidermal keratinocytes and of VEGF receptors by tortuous microvessels in the upper dermis. To investigate the functional importance of chronic VEGF overexpression in vivo, we used a keratin 14 promoter expression cassette containing the gene for murine VEGF164 to selectively target VEGF expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
406
0
6

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 516 publications
(428 citation statements)
references
References 38 publications
16
406
0
6
Order By: Relevance
“…Orf virus replication is known to be confined to the epidermis (23,24), but our data suggest that the viral VEGF affects endothelial cells of the dermis. This notion is consistent with the results of studies of transgenic mice, in which overexpression of VEGF in keratinocytes stimulated an increase in the density of blood vessels in the dermis (10). Enhanced expression of VEGF has also been reported for a range of malignant and benign tumors of the skin and has been shown for advanced melanoma lesions to directly correlate with a 2.5-fold increase in the vascular density of the associated dermis (11).…”
Section: Discussionsupporting
confidence: 89%
“…Orf virus replication is known to be confined to the epidermis (23,24), but our data suggest that the viral VEGF affects endothelial cells of the dermis. This notion is consistent with the results of studies of transgenic mice, in which overexpression of VEGF in keratinocytes stimulated an increase in the density of blood vessels in the dermis (10). Enhanced expression of VEGF has also been reported for a range of malignant and benign tumors of the skin and has been shown for advanced melanoma lesions to directly correlate with a 2.5-fold increase in the vascular density of the associated dermis (11).…”
Section: Discussionsupporting
confidence: 89%
“…38 This is consistent with the stabilizing effect of Ang1 on vascular endothelium and its underlying basement membrane. In the Matrigel model, the induction of angiogenesis in response to Ang1 also appeared to produce relatively non-leaky neovessels, because although VEGF and Ang1 resulted in similar increases in vessel number, VEGF-treated Matrigel implants contained significantly greater amounts of FITClabeled dextran.…”
Section: Discussionsupporting
confidence: 84%
“…8 Leukocyte adhesion secondary to VEGF has been previously demonstrated in the microvasculature of growing tumors, 18 the corneas of rabbits, 19 and the skin of transgenic mice. 20 Detmar and associates expressed VEGF using the keratin 14 promoter and observed the induction of a vascular cell adhesion molecule-1 (VCAM-1)-mediated leukostasis in the dermis. 20 In a separate study, Melder and associates demonstrated VEGF-induced leukocyte adhesion to tumor vasculature via ICAM-1 and VCAM-1.…”
Section: Discussionmentioning
confidence: 99%